Mechanisms of action and applications of Polygonatum sibiricum polysaccharide at the intestinal mucosa barrier: a review - Ren, Yu; Sun, Yi; Liao, Yu-Ying; Wang, Si; Liu, Qian; Duan, Chun-Yan; Sun, Lan; Li, Xiao-Ya; Yuan, Jia-Li (Frontiers in Pharmacology, 2024)
As a medicinal and edible homologous Chinese herb, Polygonatum sibiricum has been used as a primary ingredient in various functional and medicinal products. Damage to the intestinal mucosal barrier can lead to or worsen conditions such as type 2 diabetes and Alzheimer’s disease. Traditional Chinese medicine and its bioactive components can help prevent and manage these conditions by restoring the integrity of the intestinal mucosal barrier. This review delves into the mode of action of P. sibiricum polysaccharide in disease prevention and management through the restoration of the intestinal barrier. Polysaccharide from P. sibiricum effectively treats conditions by repairing the intestinal mucosal barrier, offering insights for treating complex diseases and supporting the application of P. sibiricum in clinical settings.